Innovative educational practice for impactful teaching strategies through scaffolding method / Hawa Rahmat, Chong Oi Leng and Rohaidah Mashudi - Rahmat, Hawa; Chong, Oi Leng; Mashudi, Rohaidah (Universiti Teknologi MARA, 2020)
As technology progresses in education, 21st-century educators need to use impactful instructional methods to ensure that the focus of education is on preparing today's children for the future. However, the biggest challenge for most lecturers in Multimedia University is teaching the non-graded subjects (pass or fail in nature). Since the subjects do not affect the CGPA, students were found not being serious or showing interest in the class. Consequently, it affects the learning outcome of the subject and also the psychosocial and moral of the students and lecturers. Therefore, action research using the Scaffolding method with a group of lecturers teaching non-graded subjects to see the effectiveness and impact on student’s learning. Grooming and Professional Etiquette subjects were chosen to be the focus of this study. The lecturers applied the new role of teachers in education using the scaffolding teaching method. Students were given tasks to organize a grooming and professional etiquette program while they showed groomed behavior. There were lectures and small discussions in the class before the event. There were peer discussion and collaboration before and during the event with minimum supervision from the lecturers. Survey questionnaires were distributed to the students at the end of the event/class for the particular semester. The results showed that this approach managed to boost up students’ grooming and professional etiquette as well as their class participation. They enjoyed the activities, more attentive, and confident when experiencing the task themselves rather than listening to lectures and watching videos in the class.